ANALYSIS OF FACTORS AFFECTING TECHNOLOGICAL INNOVATIVENESS IN ENGINEERING ENTERPRISES IN TANZANIA - Mjema, Emmanuel A. M (Tanzania Journal of Engineering and Technology, 2017)
This paper discusses the technological innovativeness in engineering enterprises in Tanzania and analyses the factors affecting the innovativeness. It starts by analyzing various concepts regarding innovation, then analyzed from documentary review factors affecting innovativeness and then analyzed the innovativeness in Tanzanian enterprises. From the documentary review it was learnt that the following key factors influence technological innovativeness: Existence of innovation management; Existence of market to absorb the products of innovation; Existence of partnership between the universities and the firms; Existence of positive culture and politics towards innovation; The government playing its role to influence innovation; Existence of the right knowledge; and Ability of the enterprises to access to financing institutions that support innovation.The research shows that there is hardly any fundamental innovation in Tanzania, what is presented as innovation is the copying of technologies and manufacture them using local material. The researcher established the following factors affecting the innovativeness of engineering enterprises in Tanzania: Level of education among the entrepreneurs in engineering enterprises; financing for the enterprises in Tanzania; partnership with R&D institutions; innovativeness culture; and market for Tanzanian products.